DATA ANALYTICS IN COMMERCE: LEVERAGING INSIGHTS FOR GROWTH - Deshmukh, Amarjit R; Kumar, Yashwant; Kumar, Rohtash; Sharma, Pooja (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the rapidly evolving field of commerce, data analytics has emerged as a transformative tool for driving growth and competitive advantage. This paper explores the role of data analytics in commerce, emphasizing how businesses leverage insights to make informed decisions, enhance operational efficiency, and stimulate growth. By integrating data-driven strategies, companies can uncover valuable patterns and trends that inform product development, marketing strategies, and customer engagement initiatives. The paper examines various data analytics techniques, including descriptive, diagnostic, predictive, and prescriptive analytics, and their applications in different commercial contexts. Additionally, it highlights case studies of organizations that have successfully implemented data analytics to achieve significant business outcomes. The discussion extends to the challenges of integrating data analytics into business operations, such as data quality, privacy concerns, and the need for skilled personnel. By addressing these challenges and showcasing best practices, the paper provides a comprehensive understanding of how data analytics can be effectively harnessed to drive commerce growth and innovation.